2013
DOI: 10.2139/ssrn.2323551
|View full text |Cite
|
Sign up to set email alerts
|

The Generosity Effect: Fairness in Sharing Gains and Losses

Abstract: We explore the interaction between fairness attitudes and reference dependence both theoretically and experimentally. Our theory of fairness behavior under reference-dependent preferences in the context of ultimatum games, defines fairness in the utility domain and not in the domain of dollar payments. We test our model predictions using a within-subject design with ultimatum and dictator games involving gains and losses of varying amounts. Proposers indicated their offer in gain-and (neatly comparable) loss-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…One explanation for this may be that we used a direct response method and not the strategy vector method as was used in the experiment of Neumann et al [10]. This explanation is supported by the comparison of dictator game behavior in the current study with the behavior reported in Baquero et al [37].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…One explanation for this may be that we used a direct response method and not the strategy vector method as was used in the experiment of Neumann et al [10]. This explanation is supported by the comparison of dictator game behavior in the current study with the behavior reported in Baquero et al [37].…”
Section: Discussionsupporting
confidence: 59%
“…The authors found a small but significant generosity effect, where dictators were more generous in the loss game. The major distinction between the current study and the one of Baquero et al [37] is that the latter used a strategy method, while the former did not.…”
Section: Related Literaturecontrasting
confidence: 55%
See 1 more Smart Citation
“…Many other studies have demonstrated that people exhibit enhanced concern for the welfare of others and for social norms in the loss domain than in the gain domain. Across several countries, ultimatum bargaining over losses induces higher demands from responders and higher offers from proposers than ultimatum bargaining over gains, which suggests that fairness is assigned a higher weight in the loss domain than in the gain domain (Buchan et al, 2005;Zhou and Wu, 2011;Baquero et al, 2013;Guo et al, 2013;Wu et al, 2014;Neumann et al, 2017). Likewise, fairness is more accessible, fairness norms are stronger, and resource allocation is more equal when bargaining over losses than over gains.…”
Section: Evidence That Losses (Vs Gains) Increase Prosocialitymentioning
confidence: 99%
“…Notably, the effect of the loss context on allocation behavior is mediated by enhanced fairness motivations and attenuated self-interest motives; that is, fairness concerns dominate over self-interest in the loss context (Leliveld et al, 2009). Moreover, people who act as dictators in the dictator game are intrinsically motivated to share more money with recipients in a loss domain than in a gain domain, thereby demonstrating a higher level of generosity in the loss context (Baquero et al, 2013;Yin et al, 2017;Thunström, 2019;Cochard et al, 2020). Last, people are less likely to harm others by exclusion (van Beest et al, 2003(van Beest et al, , 2005 and are more cooperative (De Dreu et al, 1992) in the loss context than in the gain context.…”
Section: Evidence That Losses (Vs Gains) Increase Prosocialitymentioning
confidence: 99%